If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33 = -2x + 5x + 9 Reorder the terms: 33 = 9 + -2x + 5x Combine like terms: -2x + 5x = 3x 33 = 9 + 3x Solving 33 = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 33 + -3x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 33 + -3x = 9 + 0 33 + -3x = 9 Add '-33' to each side of the equation. 33 + -33 + -3x = 9 + -33 Combine like terms: 33 + -33 = 0 0 + -3x = 9 + -33 -3x = 9 + -33 Combine like terms: 9 + -33 = -24 -3x = -24 Divide each side by '-3'. x = 8 Simplifying x = 8
| 9(5-k)+7=-7(k-4)-5 | | 7y+1-2y=2+4y+4 | | -3G-12=-5+G | | -24=y-7 | | 5x-10=14-3 | | 70=6(r+5)-14 | | 11t-13=4t-6 | | 24x-72=8y | | z-1.2=4.9 | | 16.75-9/4= | | 2(x+1)=3x+8 | | 2.3v=21 | | 0.6g+-11=5 | | 18x+13=157 | | 18x+x=326 | | -y-15+9y=3y+2+3y | | -2x+4=2(4x-3)-3(-8+4x) | | 2x+3/4+6/4=16.75 | | 8(x+1)=4(x-8) | | 2x+3/4+6/4= | | 147w^2-75=0 | | 3x-9-6=0 | | 70=6(e+5)-14 | | 7.3=y+5 | | 7.3=y+5 | | 2/121/4= | | y-15=-27 | | 11x+12=13x-4 | | 2+1/2= | | 4(z+2)=4+5z | | x+4=-48 | | -68-3= |